2021
DOI: 10.46306/ncabet.v1i1.59
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemimpinan Transformasional, Komitmen Organisasional, Budaya Organisasi Dan Tata Kelola Terhadap Kinerja Dosen Perguruan Tinggi Swasta Di Provinsi Banten

Abstract: This study aims to formulate a model and analyze the direct influence of Transformational Leadership, Organizational Commitment and Organizational Culture on Governance and Lecturer Performance in Private Universities in Banten. This study uses an associative quantitative approach, or research aimed at knowing the effect of exogenous variables on endogenous variables. Data collection using survey methods, and analysis techniques using SEM with Lisrel 8.80 software. The population in this study were lecturers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…This research has proven that professionalism and work discipline can be achieved to improve lecturer performance. In this regard, it was found that professionalism and work discipline can most influence Lecturer Performance (Affandi et al, 2021). Professionalism in social competence is especially reflected in the ability to express opinions.…”
Section: Discussionmentioning
confidence: 99%
“…This research has proven that professionalism and work discipline can be achieved to improve lecturer performance. In this regard, it was found that professionalism and work discipline can most influence Lecturer Performance (Affandi et al, 2021). Professionalism in social competence is especially reflected in the ability to express opinions.…”
Section: Discussionmentioning
confidence: 99%